2003
DOI: 10.2224/sbp.2003.31.4.343
|View full text |Cite
|
Sign up to set email alerts
|

Technology and Self-Regulation: The Case of Alarm Clock Use

Abstract: A study of 417 undergraduate students examined a hypothesized correlation between use of alarm clocks to awaken and self-regulatory skills. As predicted, use of awakening aids (alarm clocks, household members) was negatively correlated with self-regulation measures, while selfawakening was positively correlated with self-regulation. Also as predicted, alarm clock use had larger negative correlations with self-regulation than did being awakened by a household member. The findings suggest that people with poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Lastly, we evaluated the impact of circadian preference, as it has been reported that circadian preference might play a role in self-awakening [ 6 , 23 , 24 ]. Participants were divided into three groups (morning, intermediate, and evening type) based on their MEQ responses.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, we evaluated the impact of circadian preference, as it has been reported that circadian preference might play a role in self-awakening [ 6 , 23 , 24 ]. Participants were divided into three groups (morning, intermediate, and evening type) based on their MEQ responses.…”
Section: Methodsmentioning
confidence: 99%
“…Everyday life is filled with technologies that take over skills that people could master themselves. For example, alarm clocks automate the task of awakening at a target time, with the result that users feel incompetent at self-awakening and are completely dependent on the devices (Crabb, 2003). Use of automatic cameras similarly robs people of opportunities to develop photographic skills, and routine use of ready-to-eat foods prevents people from learning how to cook (Stern & Kipnis, 1993).…”
Section: The Incompetence Trapmentioning
confidence: 99%